Kinerja Dinas Pemberdayaan Kinerja Dinas Pemberdayaan Perempuan dan Perlindungan Anak Pengendalian Penduduk dan Keluarga Berencana Kota Tangerang dalam Penanganan Kasus Kekerasan Terhadap Anak di Kota Tangerang - Sihombing, Debby; Prafitri, Nikki; Listyaningsih, Listyaningsih (Contemporary Public Administration Review, 2024)
The problem of violence against children in Indonesia has been recognized as a serious problem and is therefore regulated by law regarding child protection and services that handle cases of violence. Banten occupies the last position of reported child violence on the island of Java with a quite drastic increase in the number of cases every year with Tangerang City as the most reported region in Banten of violence against child. Therefore, this research makes the performance of the Women's Empowerment, Child Protection, Population Control and Family Planning Department of Tangerang City in handling cases of violence against children in Tangerang City as the focus of research using descriptive research methods with a qualitative approach. The results of the research show that the performance of the Department of Women's Empowerment, Child Protection, Population Control and Family Planning in Tangerang City in handling cases of violence against children in Tangerang City has been implemented quite well, although not yet optimal. Judging from the aspects of Productivity, Service Quality, Responsiveness in handling cases of violence against children in Tangerang City, the performance of the Women's Empowerment Service for Child Protection, Population Control and Family Planning in Tangerang City is still not being implemented optimally. Despite this, the Tangerang City Department of Women's Empowerment, Child Protection, Population Control and Family Planning continues to evaluate and receive aspirations directly or online as well as holding regular meetings and continues to improve its performance in handling cases of violence against children in Tangerang City in the future.